Are We Making Progress? Assessing Goal-Directed Behaviors in Leadership Development Programs - Velasco, Ferran; Batista-Foguet, Joan Manuel; Emmerling, Robert J. (Frontiers in Psychology, 2019)
Leadership development programs increasingly help participants engage in their career transitions. Therefore, these programs lead participants to establish not only development goals, which usually involve the improvement of a specific leadership competency, but also goals that relate to career advancement or to achieving a more general life aspiration. Assessing goal attainment, as a measure of program impact, may take years as goals vary greatly in terms of nature, timeframe and domain. The purpose of this study was to overcome this challenge by providing a measure of goal progress as a necessary antecedent of goal attainment, and which we operationalize through a general scale of goal-directed behaviors. Subject-matter experts assessed the content validity of the measure. Factor analysis, using three samples, revealed four dimensions identified as Sharing Information, Seeking Information, Revising the Plan, and Enacting the Plan. This new scale allows data collection as early as a few months after setting the goals, which can provide practitioners with an earlier indication of program impact and facilitate future academic studies in this field.